Mendorong Kawasan Ramah Hak Asasi Manusia di Kabupaten Lampung Timur - Dian Suci Pratiwi; Syamsul Maarif (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2019)
Public policies are implemented in various fields, including human rights-friendly zoning policies. The policy is written in the Regulations of East Lampung Regent Number 48 of 2016 concerning Friendly District Human Rights. Where the policy is an effort to fulfill human rights to the community. East Lampung regency through understanding of the District / City bearing the first Human Rights Friendly Area in Lampung Province, in addition because it has a stigma of social conflict. This research is a descriptive study with a qualitative approach that focuses on the Practices of the Implementation of Human Rights Friendly Areas in East Lampung.. Based on the analytical framework, this study uses data analysis with the process of reducing, presenting, and verifying data, obtained from interviews, observation and documentation. Regarding the Implementation of the Policy for Human Rights-Friendly Areas in East Lampung, overall the implementation of policies has been carried out well. it's just that the implementation of funding resources has not been maximally fulfilled, thus reducing the effectiveness of implementation and implementation has added value from the communication variable.